Conversion of differentiation inducer resistance to differentiation inducer sensitivity in erythroleukemia cells. - Michaeli, J (1990)
Hexamethylene bisacetamide (HMBA) is a potent inducer of differentiation of murine erythroleukemia cells (MELC). Commitment, the irreversible initiation of the program of terminal-cell differentiation, is first detected in HMBA-sensitive DS19-SC9 MELC in culture after 10 to 12 h of exposure to HMBA. Vincristine (VC)-resistant MELC derived from the DS19-SC9 MELC line display increased sensitivity to HMBA and become committed with little or no latent period. In the present study, we showed that the MELC line R1, which is resistant to HMBA-mediated differentiation, became sensitive to inducer if selected for a low level of VC resistance (less than 10 ng of VC per ml). Four independently derived VC-resistant cell lines from HMBA-resistant R1 cells, designated R1[VCR]a to R1[VCR]d, acquired sensitivity to HMBA and the accelerated kinetics of commitment that are characteristic of VC-resistant MELC derived from the parental DS19-SC9 cells. The calcium channel blocker verapamil suppresses the VC resistance of R1[VCR] cells but does not alter the accelerated response to HMBA. In R1[VCR] cells there was no detectable increase in the level of the 140-kilodalton P-glycoprotein. Transient inhibition of protein synthesis during the latent period delays inducer-mediated commitment of VC-sensitive DS19-SC9 MELC but does not alter the accelerated commitment kinetics of R1[VCR]a cells. Previously, we have reported evidence that protein kinase C beta (PKC beta) plays a role in HMBA-induced MELC differentiation and that compared with DS19-SC9 cells, R1 cells have a relatively low level and R1[VCR]a cells have a high level of PKC beta. These findings suggest that (i) acquisition of VC resistance overcomes the block acquired by R1 cells to HMBA-mediated differentiation; (ii) the accelerated kinetics of HMBA-induced commitment of VC-resistant MELC is not dependent on the verapamil-sensitive transport channel that is responsible, at least in part, for resistance to VC; (iii) in VC-resistant MELC, there is constitutive expression or accumulation of a protein required for HMBA-induced differentiation; and (iv) an elevated level of PKC beta activity may play a role in the altered response of R1[VCR] and other VC-resistant MELC to HMBA.